Dampak Air Terhadap Perubahan Sifat Fisik, Kimia, dan Struktur Mikro Biochar dari Tandan Kosong Kelapa Sawit - Benny Hidayat; Syarifa Mayly; Dini Mufriah; Fachri Muhammad; Kemala Sari (Jurnal Penelitian Kelapa Sawit, 2026)
Water is essential to life, and immersion treatment has been shown to significantly alter the properties of biochar, particularly by converting its hydrophobic nature into a hydrophilic one and others. This transformation leads to various changes in the material's physicochemical characteristics. In this study, biochar produced through pyrolysis of oil palm empty fruit bunches (EFB) using a kiln method was analyzed to assess its physical properties before and after immersion in distilled water. Surface morphology and elemental composition were evaluated using Scanning Electron Microscopy coupled with Energy Dispersive X-ray Spectroscopy (SEM-EDX), while specific surface area was measured using the Brunauer–Emmett–Teller (BET) method. Additional analyses, including pH, bulk density, water holding capacity, and moisture content, were conducted at the National Research and Innovation Agency (BRIN) and the Soil Biology Laboratory, Faculty of Agriculture, University of North Sumatra. The results demonstrated that water immersion induced notable changes in biochar characteristics. The pH of the biochar slightly decreased from 10.09 in dry EFB biochar to 9.54 in the soaked sample. While the soaked biochar exhibited higher concentrations of most nutrient elements, the carbon (C) content remained higher in the dry biochar at 65.06%. BET analysis revealed that the surface area of dry biochar (79.446 m²/g) was substantially greater than that of the soaked biochar (38.783 m²/g). Conversely, the soaked biochar showed superior performance in terms of bulk density (0.34 g/cm³), water holding capacity (10.51%).